1996
DOI: 10.1016/s1074-5521(96)90118-0
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid probes based on Congo Red distinguish between fibrils comprising different peptides

Abstract: This study demonstrates that small organic and organometallic molecules are capable of detecting differences in amyloid fibril structure and/or amyloid protein sequence. Molecules of this type could have utility as neuropathological probes or imaging agents, since they are much easier to prepare and functionalize than antibodies and are specific for the fibrillar form of the amyloid proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 26 publications
1
41
0
Order By: Relevance
“…A previous study also showed that the binding molar ratios of CR molecules to a -type V L dimer were ϳ8 at 40-45°C and ϳ16 at 55°C, measured by gel extraction analysis (22). The dissociation constant (ϳ19 M) of CR binding to SMA is similar to that (ϳ9 M) of CR binding to A␤-amyloid fibrils determined by filtration method using radiolabeled CR (47).…”
Section: Discussionsupporting
confidence: 55%
“…A previous study also showed that the binding molar ratios of CR molecules to a -type V L dimer were ϳ8 at 40-45°C and ϳ16 at 55°C, measured by gel extraction analysis (22). The dissociation constant (ϳ19 M) of CR binding to SMA is similar to that (ϳ9 M) of CR binding to A␤-amyloid fibrils determined by filtration method using radiolabeled CR (47).…”
Section: Discussionsupporting
confidence: 55%
“…Its absorption spectrum shifts from orange-red to rose-red when it binds to fibrillar Ab1-40. CR binds to amyloid only in the b-pleated sheet conformation (Ashburn et al, 1996;Klunk et al, 1999). Because it has a high affinity for amyloid in brain slices, it is used as a targeting head group which can increase the ability of the complex to bind amyloid plaques in CR-BSA-(Gd-DTPA)n. The ability of CR-BSA-(Gd-DTPA)n to bind Ab protein was demonstrated by the histochemistry staining of APP/PS1 mouse brain sections.…”
Section: Discussionmentioning
confidence: 99%
“…An analog of CR with two methyl groups at the 2-and 2 0 -positions (2,2 0 -dimethyl-CR) was synthesized from 4-amino-1-naphthalenesulfonic acid sodium salt and 2,2 0 -dimethylbenzidine dihydrochloride (Aldrich) according to the literature method. 13 The crude product was purified by HPLC on a reversed-phase column (Cosmosil 5C18-AR). The sodium salt of unmethylated CR was purchased from Merck.…”
Section: Methodsmentioning
confidence: 99%
“…Examination of the relative affinities of several CR analogs revealed that modification of the naphthalene ring largely affects the affinity for amyloid fibrils. 13 Comparison of amyloid selectivity among CR and related dyes concluded that the central benzidine (4,4-diaminobiphenyl)-type structure of CR is essential for the selective binding to amyloid. 14 Spectroscopic studies provided a few pieces of information on the amyloid-binding sites of CR.…”
Section: Introductionmentioning
confidence: 99%